Psychological Health of Surgeons in a Time of COVID-19: A Global Survey - (:unkn) unknown (My University, 2021)
OBJECTIVE: To assess the degree of psychological impact among surgical providers during the COVID-19 pandemic. SUMMARY BACKGROUND DATA: The COVID-19 pandemic has extensively impacted global healthcare systems. We hypothesized that the degree of psychological impact would be higher for surgical providers deployed for COVID-19 work, certain surgical specialties, and for those who knew of someone diagnosed with, or who died, of COVID-19. METHODS: We conducted a global web-based survey to investigate the psychological impact of COVID-19. The primary outcomes were the Depression Anxiety Stress Scale-21 (DASS-21) and Impact of Event Scale-Revised (IES-R) scores. RESULTS: 4283 participants from 101 countries responded. 32.8%, 30.8%, 25.9% and 24.0% screened positive for depression, anxiety, stress and Post-Traumatic Stress Disorder (PTSD) respectively. Respondents who knew someone who died of COVID-19 were more likely to screen positive for depression, anxiety, stress and PTSD (OR 1.3, 1,6, 1.4, 1.7 respectively, all p < 0.05). Respondents who knew of someone diagnosed with COVID-19 were more likely to screen positive for depression, stress and PTSD (OR 1.2, 1.2 and 1.3 respectively, all p < 0.05). Surgical specialities that operated in the Head and Neck region had higher psychological distress among its surgeons. Deployment for COVID-19-related work was not associated with increased psychological distress. CONCLUSIONS: The COVID-19 pandemic may have a mental health legacy outlasting its course. The long-term impact of this ongoing traumatic event underscores the importance of longitudinal mental health care for healthcare personnel, with particular attention to those who know of someone diagnosed with, or who died of COVID-19.